Les Jésuites et la dévotion à saint Louis au xviie siècle : la célébration du Roi très chrétien - Géraldine Lavieille (Les Cahiers de Framespa)
While protected and supported by the Crown since their return to France in 1603, and yet still criticized by the most fervent Gallicans, the Jesuits paid tribute, throughout the 17th century, to the Most Christian King by worshiping Saint Louis, the new patron saint of the kingdom, whose figure mirrors that of the ruling Bourbon King. Both the worshiping and the iconography praise the royal patron and they commemorate and make public the favor of the King, against the virulent critics that the Jesuits are confronted to. In so doing, they prove their faithfulness to the ruling King and more generally to the French monarchy, while showing they have the country’s best interest at heart ; from then on, they justify their integration to France. The iconography of Saint Louis then draws a very laudatory picture of the Most Christian King both as an example and the first of the faithful, whose mission is to lead his kingdom onto the path of salvation.